Forest biomass, productivity and carbon cycling along a rainfall gradient in West Africa. (4th December 2017) - Moore, Sam; Adu‐Bredu, Stephen; Duah‐Gyamfi, Akwasi; Addo‐Danso, Shalom D.; Ibrahim, Forzia; Mbou, Armel T.; de Grandcourt, Agnès; Valentini, Riccardo; Nicolini, Giacomo; Djagbletey, Gloria; Owusu‐Afriyie, Kennedy; Gvozdevaite, Agne; et al.
Abstract: Net Primary Productivity (NPP) is one of the most important parameters in describing the functioning of any ecosystem and yet it arguably remains a poorly quantified and understood component of carbon cycling in tropical forests, especially outside of the Americas. We provide the first comprehensive analysis of NPP and its carbon allocation to woody, canopy and root growth components at contrasting lowland West African forests spanning a rainfall gradient. Using a standardized methodology to study evergreen (EF), semi‐deciduous (SDF), dry forests (DF) and woody savanna (WS), we find that (i) climate is more closely related with above and belowground C stocks than with NPP (ii) total NPP is highest in the SDF site, then the EF followed by the DF and WS and that (iii) different forest types have distinct carbon allocation patterns whereby SDF allocate in excess of 50% to canopy production and the DF and WS sites allocate 40%–50% to woody production. Furthermore, we find that (iv) compared with canopy and root growth rates the woody growth rate of these forests is a poor proxy for their overall productivity and that (v) residence time is the primary driver in the productivity‐allocation‐turnover chain for the observed spatial differences in woody, leaf and root biomass across the rainfall gradient. Through a systematic assessment of forest productivity we demonstrate the importance of directly measuring the main components of above and belowground NPP and encourage the establishment of more permanent carbon intensive monitoring plots across the tropics. Abstract : In the first comprehensive analysis of NPP and its carbon allocation to woody, canopy and root growth components at contrasting lowland West African forests spanning a rainfall gradient, we show that total NPP values are highest in semi‐deciduous forests and lowest in woody savanna with distinct patterns in carbon allocation to different growth components. Woody growth rate of these forests is a poor proxy for their overall productivity and residence time is the primary driver for the observed spatial differences in woody, leaf and root biomass across the rainfall gradient. Mean (a) total annual NPP (±1 SE) split into its components and (b) annual NPP allocation into canopy, wood and root components at each of the four vegetation types along the extended rainfall gradient plot network.